Case report: Robotic repair of unroofed coronary sinus - Pojar, Marek; Timbilla, Salifu; Cerny, Stepan; Karalko, Mikita; Vojacek, Jan (Frontiers in Cardiovascular Medicine, 2022)
Unroofed coronary sinus is a rare congenital heart disease caused by the partial or complete absence of the common wall between the coronary sinus and left atrium. When indicated for repair, it is done either percutaneously or surgically. Repair using a totally endoscopic robotic procedure is rarely performed nor reported in the literature. We report a case of a 47-year-old male who underwent a successful totally endoscopic robotic repair of this anomaly.